Analysis of Transient Characteristics of Submersible Tubular Pump During Runaway Transition - Sun, Zhuangzhuang; Yu, Jie; Tang, Fangping; Ge, Hengjun; Yuan, Haixia (Frontiers in Energy Research, 2022)
In order to study the transient characteristics of the submersible tubular pump in the process of power failure, the 6DOF model was used to carry out three unsteady numerical values for the whole flow channel of the pump. The results show that the calculation results of the 6DOF model based on the fourth-order multi-point Adams–Moulton formula are in better agreement with the experimental results than the first-order format to predict the impeller motion. When the unit is powered off, the speed and flow of the pump device decrease rapidly with time. At the maximum head 3.41 m, when the unit enters the runaway condition, the speed is about −1.88 times the initial speed and the flow rate is about −1.98 times the initial flow. The axial force and radial force of the impeller increase alternately, and compared with the normal operating condition, the radial force is significantly increased. In the process of the pump device changing from forward flow to reverse flow, the internal flow state of the pump device is relatively chaotic, and there are a large number of vortices in the flow channel, which is easy to cause structural vibration. Before reaching the runaway state, a large number of vortices also appear inside the impeller and guide vane, causing flow blockage, especially when the flow rate is zero. At the same time, the reverse flow impact causes the local pressure on the blade surface to increase, which threatens the stability of the blade structure. The pressure at the impeller inlet, impeller outlet, and guide vane outlet monitoring points is the largest near zero flow, and the smallest during runaway. The main frequency of the pressure pulsation in the pump device is the blade pass frequency (fBRF) and its harmonics (2fBRF, 3fBRF, 5fBRF, etc.), and the pressure pulsation intensity increases with the increase of the impeller speed. The results of this study provide a theoretical reference for the operation of the submersible tubular pump to ensure the safety and stability of the pumping station.